Ax2 + Bx + Cy + D = 0
Ay2 + By + Cx + D = 0
Observing the equations above, the general equation of parabola will have square for any one of the variable either x or y.
To convert this equation to standard form, we have to remember
y = a(x - h)2 + k
x = a(y - k)2 + h
Write the following equations in standard form :
Problem 1 :
y = 2x2 - 12 x + 6
Solution :
y = 2x2 - 12 x + 6
Factoring 2 from x terms,
y = 2(x2 - 6 x) + 6
y = 2[x2 - 2 x (3) + 32 - 32] + 6
y = 2[(x - 3)2 - 9] + 6
Distributing 2, we get
y = 2(x - 3)2 - 18 + 6
y = 2(x - 3)2 - 12
Problem 2 :
y = x2 - 6 x + 11
Solution :
y = x2 - 6 x + 11
y = [x2 - 2 x (3) + 32 - 32] + 11
y = [(x - 3)2 - 32] + 11
y = [(x - 3)2 - 9] + 11
y = (x - 3)2 - 9 + 11
y = (x - 3)2 + 2
Problem 3 :
x = y2 + 14y + 20
Solution :
x = y2 + 14y + 20
x = [y2 + 2 x (7) + 72 - 72] + 20
x = [(y + 7)2 - 72] + 20
x = (y + 7)2 - 49 + 20
x = (y + 7)2 - 29
Problem 4 :
y = (1/2) x2 + 12x - 8
Solution :
y = (1/2) x2 + 12x - 8
Factoring 1/2 from x2 and x, we get
y = (1/2)[x2 + 24x] - 8
y = (1/2)[x2 + 2 x (12) + 122 - 122] - 8
y = (1/2)[(x + 12)2 - 144] - 8
Distributing 1/2, we get
y = (1/2)(x + 12)2 - 72 - 8
y = (1/2)(x + 12)2 - 80
Problem 5 :
x = 3y2 + 5y - 9
Solution :
x = 3y2 + 5y - 9
Factoring 3 from y terms it is not possible, because the coefficient of y is not a multiple of 3.
x = 3[y2 + (5/3)y] - 9
Writing the coefficient of x as multiple of 2, we get
x = 3[y2 + 2(5/6)y + (5/6)2 - (5/6)2] - 9
x = 3[(y + (5/6))2 - (25/36)] - 9
x = 3(y + (5/6))2 - (25/12) - 9
x = 3(y + (5/6))2 + (-25 - 108)/12
x = 3(y + (5/6))2 + (-133)/12
Problem 6 :
Katie is finding the standard form of the equation
y = x2 + 6x + 4
Solution :
y = x2 + 6x + 4
y = x2 + 2 x (3) + 32 - 32 + 4
y = (x + 3)2 - 32 + 4
y = (x + 3)2 - 9 + 4
y = (x + 3)2 - 5
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM